Challenges in mapping European rare disease databases, relevant for ML-based screening technologies in terms of organizational, FAIR and legal principles: scoping review - Raycheva, Ralitsa; Kostadinov, Kostadin; Mitova, Elena; Bogoeva, Nataliya; Iskrov, Georgi; Stefanov, Georgi; Stefanov, Rumen (Frontiers in Public Health, 2023)
Given the increased availability of data sources such as HISs, EHRs, and health-related registries, a novel approach is required to develop artificial intelligence-based decision support that can assist clinicians in their diagnostic decisions. The aim is to identify key challenges in the process of mapping European rare disease databases, relevant to ML-based screening technologies in terms of organizational, FAIR and legal principles. A scoping review was conducted based on the PRISMA-ScR checklist. The primary article search was conducted in MEDLINE/Pubmed, Scopus, and Web of Science and a secondary search was performed in Google Scholar and on the organizations' websites. At the end of the screening process, 73 studies were eligible for review based on inclusion and exclusion criteria with more than 60% (n=46) of the research published in the last 5 years and originated only from EU/EEA countries. Over the ten-year period (2013-2022), there is a clear cycling trend in the publications, with a peak of challenges reporting every four years. Except for 2016, organizational challenges dominated the articles published up to 2018; legal challenges were the most frequently discussed topic from 2018 to 2022. The following distribution of the data items by domains was observed - 1) organizational: data accessibility and sharing (20.2%); long-term sustainability (18.2%); governance, planning and design (17.2%); lack of harmonization and standardization (17.2%); quality of data collection (16.2%); and privacy risks and small sample size (11.1%); 2) FAIR: findable (17.9%); accessible sustainability (25.0%); interoperable (39.3%); and reusable (17.9%); This is a provisional file, not the final typeset article and 3) legal: data protection (34.4%); data management and ownership (22.9%); research under GDPR (20.8%); trust and transparency (13.5%); and digitalization of health (8.3%). The proportion of publications addressing good practices, guidelines, and recommendations for overcoming challenges when mapping RD databases in at least one domain was calculated to be 47.9% (n=35). Despite the opportunities provided by innovation, the results of the current scoping review demonstrate a diversity of the challenges that must still be addressed, with immediate actions on ensuring better governance of rare disease registries, implementing FAIR principles, and enhancing the EU legal framework.